Biomechanical analysis of lower-limb asymmetry in chinese speed skating national team athletes - Shu, Y.; Liang, Z.; Ma, M.; Feng, J.; Wei, X.; Song, Q.; Chen, X. (Journal of Shanghai University of Sport, 2023)
Objective To investigate the performance of bilateral asymmetry in speed skaters using conventional asymmetry testing methods and skating training device to simulate speed skating bend stance.